Evaluation of the efficacy of shadowing house officer experience in surgical training - Kanchana Wijesinghe; Aruni Jayasinghe; Hasangi Gamage; Thushan Gooneratne; Yohan Chamara; Malith Nandasena; Umesh Jayarajah; Aloka Pathirana; Deepaka Weerasekara (Springer, 2024)
Abstract Background The shadowing house officer is an experiential learning activity that usually takes place within the final year clinical rotations of medical undergraduates. An exposure to a surgical intern is especially useful as the work extends to more practical aspects of ward work. Objective We assessed the impact of the shadowing house officer exprience during medical student clinical rotation on the surgical internship and to evaluate the challenges of the shadowing period. Methods A descriptive cross-sectional survey was carried out among 108 surgical intern doctors in Sri Lanka via electronic media in 2023. Results Our study population consisted of 108 interns, with a response rate of 43.2%. This study demonstrates that on average a final year medical student undergoes a 4- day shadowing period in surgery which was considered by a majority to help in smooth transition to internship. 56% had a clear understanding about learning outcomes and less than half has had an induction session prior to commencement of shadowing. Official documentation, routine ward work, team work and communication skills were meaningfully experienced during shadowing. The main criticisms were inadequate breaks leading to exhaustion and missing out on important teaching activities. Another major concern was shadowing close to the final examination. Conclusions Surgical shadowing house officer is an authentic work experience that intern doctors consider as important component in orientating the role of an intern. Introduction of shadowing at an earlier stage would be more beneficial and provide a broader view about the clinical set up to undergraduates.